A valley-spin qubit in a carbon nanotube - Laird, E; Pei, F; Kouwenhoven, L (2013)
Although electron spins in III-V semiconductor quantum dots have shown great promise as qubits, hyperfine decoherence remains a major challenge in these materials. Group IV semiconductors possess dominant nuclear species that are spinless, allowing qubit coherence times up to 2 s. In carbon nanotubes, where the spin-orbit interaction allows for all-electrical qubit manipulation, theoretical predictions of the coherence time vary by at least six orders of magnitude and range up to 10 s or more. Here, we realize a qubit encoded in two nanotube valley-spin states, with coherent manipulation via electrically driven spin resonance mediated by a bend in the nanotube. Readout uses Pauli blockade leakage current through a double quantum dot. Arbitrary qubit rotations are demonstrated and the coherence time is measured for the first time via Hahn echo, allowing comparison with theoretical predictions. The coherence time is found to be ∼65 ns, probably limited by electrical noise. This shows that, even with low nuclear spin abundance, coherence can be strongly degraded if the qubit states are coupled to electric fields. © 2013 Macmillan Publishers Limited. All rights reserved.